PENGARUH LISTED, KEPEMILIKAN SAHAM OLEH INSTITUSIONAL DAN NILAI TUKAR TERHADAP PROFITABILITAS PERBANKAN DOMESTIK DI INDONESIA - Rahmadhani, Sari (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2010)
The research problem is the decrease of profitability happened in the year of 2005 and 2007. The condition indicates the existence of serious problem on banking profitability. The other problem was showed by the existence or research gap of some factors which influence on banking profitability. The samples of research are 62 domestic banks, by using multiple regression analysis. The result of this research only the listed positively and significantly influence on banking profitability, if the ownership of stock by company and exchange rate insignificantly not influence on banking profitability